2013
DOI: 10.1007/s12291-013-0332-1
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Trimester-Specific Reference Intervals of Serum TSH & fT4 in a Pregnant Indian Population at North Kolkata

Abstract: Reference intervals (RIs) of serum thyroid stimulating hormone (TSH) and free thyroxine (fT4) were determined in 402 healthy pregnant women by enzyme-linked immunosorbent assay (ELISA) technique after partitioning them into three trimesters. The reference population was chosen from a study population of 610 pregnant females by applying strict inclusion and exclusion criteria. The assays were done using proper quality control measures. RIs were calculated from the central 95 % of the distribution of TSH and fT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…[101112141516171819202122232425] Soldin et al . [15] showed that FT4 decreased from the 1 st to 3 rd trimester ( P < 0.001), but there was no significant difference between the second to the third trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[101112141516171819202122232425] Soldin et al . [15] showed that FT4 decreased from the 1 st to 3 rd trimester ( P < 0.001), but there was no significant difference between the second to the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…In India, limited data's are available over trimester-specific thyroid hormones level during pregnancy and none from Haryana. [89101112] The aim of this study was to establish trimester-specific reference range for thyroid hormone during pregnancy in a tertiary care center in Haryana which is an iodine sufficient area of India.…”
Section: Introductionmentioning
confidence: 99%
“…Untreated and undetected gestational thyroid disorders are known to cause many complications like anemia, pregnancy-induced hypertension , hemorrhage, preterm delivery in mothers, and low birth weight, prematurity, congenital malformation, intrauterine fetal death, and lower intelligence quotient in children. 12 In recent years, various studies recommend the use of routine thyroid function tests for screening of thyroid disease during normal antenatal checkup. 13,14 Hence, selection and proper interpretation of gestational thyroid function parameters are important for the well-being of both the mother and the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated and undetected gestational thyroid disorders are known to cause many complications like anemia, pregnancy-induced hypertension, hemorrhage, preterm delivery in mothers and low birth weight, prematurity, congenital malformation, intrauterine fetal death, and lower intelligence quotient in children. 12 In recent years, various studies recommend the use of routine thyroid function tests for screening of thyroid disease during normal antenatal checkup (ANC). 13,14 Hence, selection and proper interpretation of gestational thyroid function parameters are important for the wellbeing of both the mother and the fetus.…”
Section: Discussionmentioning
confidence: 99%